Effect of mesostructure on quasi-static and dynamic tensile strength of rock: insights from a breakable grain-based model - Cheng Pan; Xing Li; Guangming Zhao; Bing Cheng (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Accurately predicting rock tensile strength under varying strain rates is crucial for tunnel construction, as rock often fails in tension. This study examines the effect of rock mesostructure on tensile strength using a breakable grain-based model (GBM) implemented within the UDEC software. The Brazilian disk model was established to simulate the quasi-static and dynamic tensile behaviors of rocks under varying mineral average grain sizes, grain size distributions, and grain roundness, respectively. Simulation outcomes indicate that mesostructure significantly influences rock tensile strength. The breakable GBM effectively captures the tensile failure process under high strain rates, revealing the role of grain structure heterogeneity in strain rate effects. Additionally, the study evaluates the applicability of different dynamic increase factor (DIF) models, confirming the effectiveness of the normalized DIF model for predicting the dynamic tensile strength of granite. These findings underscore the importance of considering rock mesostructure for accurate prediction and enhancement of rock performance under dynamic loading conditions.